Infrastructure, Economic Growth, and Poverty : A Review - Timilsina, Govinda; Hochman, Gal; Song, Ze (World Bank, Washington, DC, 2020)
How much an economy should invest in its physical infrastructure is a crucial question being asked by policy makers from developing countries where financial resources for economic development are limited. This paper aims to address this question by bringing insights from the literature that investigates the relationship between infrastructure investment, economic growth, and poverty alleviation. The study shows that there is no consensus among the existing studies, which are mostly focused on industrialized economies, on the relationship between public investment and economic growth. Studies that investigate the relationship between physical infrastructure and economic growth mostly conclude that there exists a positive relationship. This is also true between physical infrastructure and income inequality, as reported by a few studies. This study also identifies many gaps in the literature and highlights the need for further studies to narrow them.